New explicit soliton solutions for the generalized coupled integrable disperssionless system - Batool, Fiza; Rezazadeh, Hadi; Akinyemi, Lanre; İnç, Mustafa (Springer, 2022)
The (G'/G)-expansion and exponential rational function methods (ERFM) are proposed for generating the precise solutions of a generalized coupled integrable dispersionless system that occurs in the study of a variety of problems in applied mathematics and physics. The current study validates the key characteristics of the techniques used, and precise kink solutions are obtained using the established procedures.
Keywords: Generalized coupled dispersionless system; Soliton solutions; (G '/G)-expansion; ERFM